Bulletin : Institute for the Study of the USSR - Institut zur Erforschung der UdSSR. (Institute for the Study of the USSR, 1954)
Title before 1955, No. 10: Bulletin of the Institute for the Study of the History and Culture of the USSR.Continues: Bulletin of the Institute for the Study of the History and Culture of the USSR.